Pharmacokinetics and safety of highly variable valsartan in single-pill combination with amlodipine versus its generic formulation: a randomized, three-cycle, three-sequence, partially replicated crossover phase I bioequivalence clinical trial - Qiu, Bo; Song, Haojing; Ding, Congyang; Sun, Xue; Du, Runxuan; Yang, Haotian; Bai, Wanjun; Dong, Zhanjun (Frontiers in Pharmacology, 2023)
Valsartan/amlodipine (I) is a single-pill combination (SPC) of an angiotensin II receptor blocker (ARB) and a calcium channel blocker (CCB) for treating hypertension. A clinical trial was performed to demonstrate that the test and reference valsartan/amlodipine formulations were bioequivalent under fasting and postprandial conditions. Participants were randomly divided into three sequences at a ratio of 1:1:1 for three -cycle, reference formulation replicated, crossover administration. The average bioequivalence (ABE) and reference-scaled average bioequivalence (RSABE) methods were used to evaluate BE using the main pharmacokinetic (PK) parameters.Overall, 45 eligible participants were enrolled in the postprandial trial, which was consistent with the fasting trial. For valsartan, the RSABE method was used to evaluate the BE of Cmax, while the ABE method was applied to evaluate the BE of AUC0-t and AUC0-∞. Both point estimates and 95% upper confidence bound met the BE criteria. For amlodipine, the ABE method was performed, and the 90% confidence intervals of the geometric mean ratios (GMR) for Cmax and AUC0-72 h were all within 80-125%, with the BE criteria being met. Therefore, the two formulations are bioequivalent and have similar safety profiles in healthy Chinese subjects.This trial was registered on the Chinese Clinical Trial website (http://www.chinadrugtrials.org.cn/index.html # CTR20210214)